A Dramatistic Analysis of the Divisoria merchant - Becodo, Ricky P. (The Philippine Journal of Development Communication, 2011)
This study looked into the communicative actions and interactions of the Divisoria vegetable market merchants based on Kenneth Burke's dramatistic theoretical perspective. By employing the Pentad to the context of Divisoria merchants, the dynamic social dramas of the merchants being "on stage and backstage" we're apparent.